Nanometer silicon composite material, preparation method and application thereof, and battery

By using alkaline earth metal and silicon powder to prepare metal silicides in the preparation of nano-silicon materials, and solvothermal reactions with silicon tetrachloride and metal sulfide nanosheets, the low utilization rate and cost of silicon source during the preparation of nano-silicon materials are solved. The problem of high performance and low cost nano-silicon composite material preparation is achieved, improving the rate performance and cycle life of the battery.

CN119400832APending Publication Date: 2025-02-07无锡锂凰科技有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411549138.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-01
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

In the prior art, there are problems in the preparation process of nano-silicon materials with low utilization rate, high production cost, and poor charging and discharging performance of large-scale.

Method used

The nano-silicon composite material was generated by preparing metal silicides using alkaline earth metal and silicon powder and undergoing solvothermal reaction with silicon tetrachloride and metal sulfide nanosheets. This method improves silicon atom utilization, reduces preparation costs, and achieves uniform dispersion of nanosilicon in the three-dimensional structure of high-ion/electron transport materials.

Benefits of technology

High-performance and low-cost preparation of nano-silicon composites is achieved, improving the rate performance and cycle life of the battery, and reducing capacity attenuation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119400832A_ABST
    Figure CN119400832A_ABST
Patent Text Reader

Abstract

The invention discloses a nano silicon composite material, a preparation method and application thereof and a battery. The preparation method of the nano-silicon composite material comprises the following steps: (1) calcining a mixture of alkaline earth metal and silicon powder for 2-12 hours at 300-800 DEG C under the protection of inert gas to prepare metal silicide; (2) performing solvothermal reaction on a mixture of metal silicide, silicon tetrachloride and the metal sulfide nanosheet to obtain a nano-silicon composite material; the molar ratio of the metal silicide to the silicon tetrachloride is 1: (1-10), the molar ratio of the metal silicide to the metal sulfide nanosheet is 1: (0.005-0.2), the temperature of the solvothermal reaction is 300-500 DEG C, and the time of the solvothermal reaction is 8-48 hours. According to the nano-silicon composite material prepared by the method, small-size silicon is coated in the high-ion-conductivity nanosheets, so that expansion can be inhibited, side reaction can be reduced, and the nano-silicon composite material has relatively good cycle life and rate capability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention specifically relates to a nano silicon composite material and a preparation method, application and battery thereof. Background Art

[0002] The theoretical specific capacity of silicon negative electrode materials is as high as 4200mAh / g. Compared with traditional graphite negative electrodes, silicon-based negative electrodes can achieve higher battery life in lithium-ion batteries. However, silicon will undergo significant volume expansion during the charging and discharging process, causing the electrode material to pulverize and destroy the electrode structure. In addition, serious side reactions will occur when silicon comes into contact with the electrolyte, which seriously affects the battery's cycle performance and restricts its application in batteries. At present, the industry's technology mainly reduces the above effects by nano-sizing bulk silicon materials, including sand milling and silane deposition on porous carbon, which have high industrialization potential.

[0003] Among them, the pyrolysis and deposition of silane in porous carbon can achieve uniform dispersion of nano-sized particles in the carbon structure, prevent silicon aggregation, inhibit silicon expansion and pulverization, and usually achieve higher specific capacity and cycle life. It is considered to be an important high-performance silicon negative electrode technology route. However, in this method, the silicon source used is a single silane, the deposition process has large losses, and professional deposition equipment is required, so the cost is relatively high. Although the sand milling method for preparing nano-silicon has a low silicon source cost, it is difficult to achieve uniform dispersion of nano-silicon in the conductive carrier material, and the performance is usually difficult to surpass that of nano-silicon prepared by silane deposition. Therefore, it is urgent to develop a nano-silicon preparation method that combines low cost and high performance to meet the needs of high-performance negative electrode applications. Summary of the invention

[0004] The technical problem solved by the present invention is to overcome the problems of low silicon source utilization, high production cost, poor high-rate charge and discharge performance, etc. in the process of preparing nano-silicon materials in the prior art, and provide a nano-silicon composite material and its preparation method, application and battery. The preparation method of the nano-silicon composite material of the present invention has high silicon atom utilization rate, can reduce the preparation cost by partially using low-cost silicon sources such as silicon powder, and realizes uniform dispersion of nano-silicon in the three-dimensional structure of high ion / electron transport materials, has the advantages of high performance and low cost, and utilizes industrial production.

[0005] The present invention first uses alkaline earth metal and silicon powder to prepare a metal silicon compound A2Si, and then conducts a solvothermal reaction on A2Si, silicon tetrachloride and metal sulfide nanosheets. During the solvothermal reaction, A2Si reacts with SiCl4 to generate nano-silicon and metal chloride, while the confinement effect of the metal sulfide nanosheets can uniformly disperse and fix the nano-silicon particles to prevent them from agglomerating, thereby inhibiting the expansion of silicon during the charge and discharge process. In addition, the metal sulfide nanosheets can also provide additional capacity, enhance the ion / electron transport performance of the negative electrode material, improve the rate performance and reduce capacity attenuation.

[0006] The present invention solves the above technical problems through the following technical solutions:

[0007] The present invention provides a method for preparing a nano-silicon composite material, which comprises the following steps:

[0008] (1) calcining a mixture of alkaline earth metal and silicon powder at 300-800° C. for 2-12 h under inert gas protection to prepare a metal silicide;

[0009] (2) subjecting the mixture of the metal silicide, silicon tetrachloride and metal sulfide nanosheets to a solvothermal reaction to obtain the nano-silicon composite material;

[0010] The molar ratio of the metal silicide to the silicon tetrachloride is 1:(1-10), the molar ratio of the metal silicide to the metal sulfide nanosheet is 1:(0.005-0.2), the temperature of the solvothermal reaction is 300-500°C, and the time of the solvothermal reaction is 8-48h.

[0011] In step (1), the alkaline earth metal may be one or more of Mg, Ca, Sr and Ba, preferably Ca and / or Mg.

[0012] In step (1), the size of the silicon powder may be 100 nm-5 μm, preferably 100 nm-2 μm.

[0013] In step (1), the molar ratio of the alkaline earth metal to the silicon powder may be 4:(1.8-6), preferably 4:(1.5-3), for example 4:1.8, 4:1.9 or 4:2.

[0014] In step (1), the inert gas may be any conventional gas in the art, generally referring to a gas that does not react with the reactants, such as nitrogen, argon or helium.

[0015] In step (1), the rate of increasing the temperature to the calcination temperature may be 2-5°C / min.

[0016] In step (1), the calcination temperature is preferably 300-500°C, such as 380°C, 400°C or 450°C.

[0017] In step (1), the calcination time is preferably 4-8 hours, for example 6 hours.

[0018] In step (1), the calcination is generally carried out in a tubular furnace.

[0019] In step (1), the chemical formula of the metal silicide may be A x Si, preferably, 0.5≤x≤3, such as 0.5, 1 or 2, and A is an alkaline earth metal as described above.

[0020] In step (2), the metal sulfide may be one or more of TiS2, NbS2, TaS2, Mo2S3, MoS2 and WS2. The thickness of the metal sulfide nanosheet may be 5nm-500nm. The morphology of the metal sulfide nanosheet is generally layered.

[0021] In step (2), the method for preparing the metal sulfide nanosheets preferably comprises the following steps:

[0022] The metal sulfide powder is ground into a suspension, mixed at a rotation speed of 4000-8000 rpm for 10-30 minutes, and then freeze-dried.

[0023] The metal sulfide powder can be obtained from conventional commercial sources or prepared by itself, for example, by solid phase reaction of a metal element and a sulfur element.

[0024] The grinding method can be conventional in the art, such as mechanical ball milling. The grinding speed can be 2000-4000 rpm, such as 3000 rpm. The grinding time can be 5-20 min, such as 10 min. A small amount of solvent, such as ethanol or deionized water, is generally added during the grinding process. The amount of the solvent is generally sufficient to wet the metal sulfide powder.

[0025] The solvent in the suspension may be one or more of ethanol, isopropanol, chloroform and DMSO. The concentration of the suspension may be 10-20 g / L, preferably 12-18 g / L, such as 15 g / L.

[0026] Wherein, during the mixing process, the metal sulfide is peeled into the form of nanosheets by utilizing the peeling effect of shear force. The mixing is generally carried out in a mixing agitator, such as a Silverson L5M agitator. During the mixing process, in order to prevent the temperature from rising, the suspension is generally kept in an ice bath. The mixing speed is preferably 5000-7000rpm, such as 6000rpm. The mixing time is preferably 15-25min, such as 20min.

[0027] The freeze-drying operation and conditions may be conventional in the art.

[0028] In step (2), the molar ratio of the metal silicide to the silicon tetrachloride is preferably 1:(1-5), such as 1:1, 1:2, 1:2.5 or 1:3.

[0029] In step (2), the molar ratio of the metal silicide to the metal sulfide nanosheets is preferably 1:(0.01-0.1), such as 1:0.01, 1:0.02, 1:0.025 or 1:0.5.

[0030] In step (2), the solvent thermal reaction is generally carried out in a reaction vessel.

[0031] In step (2), the rate of heating to the temperature of the solvothermal reaction may be 1-5°C / min.

[0032] In step (2), the temperature of the solvothermal reaction is preferably 300-400°C, such as 350°C, 380°C or 400°C.

[0033] In step (2), the solvent thermal reaction time is preferably 8-24 h, such as 10 h, 15 h or 20 h.

[0034] In step (2), according to the conventional art, washing and drying are generally required after the solvent thermal reaction is completed. The solvent used in the washing process can be conventional in the art, generally deionized water and / or ethanol. The number of washing times can be 3-6 times.

[0035] The present invention also provides a nano-silicon composite material prepared by the above-mentioned preparation method.

[0036] The present invention also provides an application of the nano-silicon composite material as described above in a battery. The battery is preferably a lithium-ion battery.

[0037] On the basis of being in accordance with the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.

[0038] The reagents and raw materials used in the present invention are commercially available.

[0039] The positive and progressive effects of the present invention are:

[0040] The nano-silicon composite material prepared by the present invention has a higher silicon atom utilization rate than that of the silane vapor deposition method. The preparation cost can be reduced by partially using low-cost silicon sources such as silicon powder, and nano-silicon can be efficiently dispersed evenly in the three-dimensional structure of high ion / electron transport materials to avoid silicon agglomeration and inhibit silicon expansion during charging and discharging. In addition, metal sulfide nanosheets can provide additional capacity and improve rate characteristics, and have the advantages of high-performance and low-cost preparation, and can be used for industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] Figure 1 This is a SEM image of the nano-silicon composite material prepared in Example 1;

[0042] Figure 2TEM image of the nano-silicon composite material prepared in Example 1;

[0043] Figure 3 This is the XRD pattern of the metal silicide Ca2Si prepared in Example 1. DETAILED DESCRIPTION

[0044] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.

[0045] The silicon powder used in the following examples and comparative examples was purchased from Aladdin, and had a purity of 99.9% and a particle size of about 1 μm.

[0046] Example 1

[0047] (1) Mixing metallic calcium powder and silicon powder in a molar ratio of 2:1 and placing them in a crucible, heating them to 450°C at a heating rate of 3°C / min in a nitrogen atmosphere of a tube furnace, keeping the temperature for 6 hours and then cooling them naturally to room temperature to obtain metal silicide Ca2Si;

[0048] (2) Preparation of TiS2 nanosheets: A small amount of ethanol was added to TiS2 powder (Beike Nano, high purity) to wet the powder, and then the powder was mechanically ball-milled at a speed of 3000 rpm for 10 min to obtain a micron-shaped flaky material; then ethanol was added to the micron-shaped flaky material to prepare a 15 g / L ethanol suspension, and the suspension was rotated at a speed of 6000 rpm for 20 min using a Silverson L5M stirrer. The suspension was always kept in an ice bath to prevent the temperature from rising. After the rotation, the suspension was freeze-dried to obtain TiS2 nanosheets;

[0049] (3) After mixing Ca2Si, TiS2 nanosheets and SiCl4 in a molar ratio of 2:0.05:5, the mixture was transferred to a reactor for solvothermal reaction. The temperature was increased to 350°C at a heating rate of 3°C / min, and the mixture was kept at this temperature for 10 h. The mixture was then cooled to room temperature, washed three times with deionized water and ethanol, and dried to obtain a nano-silicon composite material.

[0050] Example 2

[0051] Compared with Example 1, except that the metal calcium powder in step (1) is replaced by metal magnesium powder and the heating temperature is changed to 380° C., other conditions remain unchanged.

[0052] Example 3

[0053] Step (1): same as in Example 1;

[0054] Step (2) Preparation of Mo2S3 nanosheets: A small amount of ethanol was added to Mo2S3 powder (Beike Nano, high purity) to wet the Mo2S3 powder, and then the powder was mechanically milled at a speed of 3000 rpm. 10min to obtain micron flake material; then Add ethanol to the rice flake material to make 15g / L The ethanol suspension was rotated at 6000 rpm for 20 min using a Silverson L5M stirrer. The suspension was always kept in an ice bath to prevent the temperature from rising. After the rotation, the suspension was freeze-dried to obtain Mo2S3 nanosheets.

[0055] Step (3): Mix Ca2Si, Mo2S3 nanosheets and SiCl4 in a molar ratio of 2:0.05:5, transfer to a reactor for solvothermal reaction, heat to 350°C at a heating rate of 3°C / min, keep warm for 10 hours, cool to room temperature, wash three times with water and ethanol respectively, and obtain a nano-silicon composite material after drying.

[0056] Example 4

[0057] Compared with Example 1, except that the molar ratio of Ca2Si, TiS2 nanosheets and SiCl4 in step (3) is adjusted to 2:0.02:5, the other parameters and conditions are the same as those in Example 1.

[0058] Example 5

[0059] Compared with Example 1, except that the molar ratio of Ca2Si, TiS2 nanosheets and SiCl4 in step (3) is adjusted to 2:0.05:2, the other parameters and conditions are the same as those in Example 1.

[0060] Example 6

[0061] Compared with Example 1, except that the temperature of the solvent thermal reaction in step (3) is adjusted to 400° C., the other parameters and conditions are the same as those in Example 1.

[0062] Example 7

[0063] Compared with Example 1, except that the holding time of the solvent thermal reaction in step (3) is adjusted to 20 hours, the other parameters and conditions are the same as those in Example 1.

[0064] Comparative Example 1

[0065] 330nm silicon powder (the purchased silicon powder was crushed to D using ethanol medium sand mill 50 is 330nm).

[0066] Comparative Example 2

[0067] (1) Mixing metallic calcium powder and silicon powder in a molar ratio of 2:1 and placing them in a crucible, heating them to 450°C at a heating rate of 3°C / min in a nitrogen atmosphere of a tube furnace, keeping the temperature for 6 hours and then cooling them naturally to room temperature to obtain metal silicide Ca2Si;

[0068] (2) Ca2Si and SiCl4 were mixed in a molar ratio of 2:5 and transferred to a reactor for solvothermal reaction. The temperature was increased to 350°C at a heating rate of 3°C / min, kept at that temperature for 10 h, cooled to room temperature, washed three times with water and ethanol respectively, and dried to obtain a nano-silicon composite material.

[0069] Effect Example

[0070] (1) Morphology characterization and XRD testing

[0071] Figure 1 This is a SEM image of the nano-silicon composite material prepared in Example 1; Figure 2 This is a TEM image of the nano-silicon composite material prepared in Example 1; according to the TEM image, it can be seen that under the confinement effect of the nanosheet, the silicon nanoparticles can be dispersed more evenly on the surface of the nanosheet.

[0072] Figure 3 This is the XRD pattern of the metal silicide Ca2Si prepared in Example 1.

[0073] (2) Electrochemical performance test

[0074] The nano-silicon composite materials prepared in Examples 1-7 and the materials prepared in Comparative Examples 1-2 were subjected to half-cell tests. The test method is: the above-mentioned materials to be tested are uniformly mixed with the binder CMC (sodium carboxymethyl cellulose) and the conductive carbon black in a mass ratio of 85:5:10, adjusted into a slurry, coated on a copper foil with a coating thickness of 100 microns, and dried at 90°C in vacuum for 12 hours to prepare a lithium battery negative electrode sheet. The simulated battery assembly was carried out in an argon-filled glove box, using a 1 mol / L LiPF6 electrolyte (the solvent is EC, EMC and DMC, EC:EMC:DMC=1:1:1 (volume ratio), a polypropylene microporous membrane as a diaphragm, and a metal lithium sheet as a counter electrode. The electrochemical performance test was carried out on a Land CT2001A battery tester at a temperature of 20°C and a charge and discharge voltage range of 0.01 to 1.5V (1C=250mAh g -1 ). The test results are shown in Table 1.

[0075] Table 1

[0076]

[0077]

[0078] According to Table 1, the nano-silicon composite material prepared by the present invention has a higher specific capacity and a better cycle life. Comparing Example 1 with Comparative Examples 1-2, it can be found that when only silicon powder is used or metal sulfide nanosheets are not added during the material preparation process, the specific capacity and cycle life will deteriorate.

[0079] Although the specific embodiments of the present invention are described above, it should be understood by those skilled in the art that this is only for illustration and the protection scope of the present invention is defined by the appended claims. Those skilled in the art may make various changes or modifications to these embodiments without departing from the principles and essence of the present invention, but these changes and modifications all fall within the protection scope of the present invention.

Claims

1. A method for preparing a nano-silicon composite material, characterized in that: The following steps are involved: (1) calcining a mixture of alkaline earth metal and silicon powder at 300-800° C. for 2-12 h under inert gas protection to prepare a metal silicide; (2) subjecting the mixture of the metal silicide, silicon tetrachloride and metal sulfide nanosheets to a solvothermal reaction to obtain the nano-silicon composite material; The molar ratio of the metal silicide to the silicon tetrachloride is 1:(1-10), the molar ratio of the metal silicide to the metal sulfide nanosheet is 1:(0.005-0.2), the temperature of the solvothermal reaction is 300-500°C, and the time of the solvothermal reaction is 8-48h.

2. The method for preparing a nano-silicon composite material according to claim 1, characterized in that: In step (1), the alkaline earth metal is one or more of Mg, Ca, Sr and Ba, preferably Ca and / or Mg; And / or, in step (1), the size of the silicon powder is 100 nm-5 μm, preferably 100 nm-2 μm.

3. The method for preparing the nano-silicon composite material according to claim 1, characterized in that: The molar ratio of the alkaline earth metal to the silicon powder is 4:(1.8-6), preferably 4:(1.5-3), such as 4:1.8, 4:1.9 or 4:

2.

4. The method for preparing the nano-silicon composite material according to claim 1, characterized in that: In step (1), the calcination temperature is 300-500°C, for example, 380°C, 400°C or 450°C; And / or, in step (1), the calcination time is preferably 4-8 hours, such as 6 hours.

5. The method for preparing the nano-silicon composite material according to claim 1, characterized in that: In step (2), the metal sulfide is one or more of TiS2, NbS2, TaS2, Mo2S3, MoS2 and WS2; And / or, the thickness of the metal sulfide nanosheet is 5nm-500nm; And / or, in step (2), the method for preparing the metal sulfide nanosheets comprises the following steps: The metal sulfide powder is ground into a suspension, mixed at a rotation speed of 4000-8000 rpm for 10-30 minutes, and then freeze-dried.

6. The method for preparing the nano-silicon composite material according to claim 5, characterized in that: The method for preparing the metal sulfide nanosheets satisfies one or more of the following conditions: (1) The grinding speed is 2000-4000 rpm; (2) The grinding time is 5-20 min; (3) The solvent in the suspension is one or more of ethanol, isopropanol, chloroform and DMSO; (4) The concentration of the suspension is 10-20 g / L.

7. The method for preparing a nano-silicon composite material according to claim 1, characterized in that: In step (2), the molar ratio of the metal silicide to the silicon tetrachloride is 1:(1-5), for example, 1:1, 1:2, 1:2.5 or 1:3; And / or, in step (2), the molar ratio of the metal silicide to the metal sulfide nanosheets is 1:(0.01-0.1), for example, 1:0.01, 1:0.02, 1:0.025 or 1:0.

5.

8. The method for preparing the nano-silicon composite material according to claim 1, characterized in that: In step (2), the temperature of the solvothermal reaction is 300-400° C., for example, 350° C., 380° C. or 400° C.; And / or, in step (2), the solvent thermal reaction time is 8-24 hours, such as 10 hours, 15 hours or 20 hours.

9. A nano-silicon composite material, characterized in that: The nano-silicon composite material is prepared according to the method for preparing the nano-silicon composite material as described in any one of claims 1 to 8.

10. Use of the nano-silicon composite material as claimed in claim 9 in a battery.